The Principal as Maker of a Local Innovation Policy Linking Research to Practice - Vandenberghe, Roland ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
The general meaning of research data drawn from study of school improvement programs creates the opportunity for sound theory building. By emphasizing the principal's role in policy development, this paper analyzes the characteristics of large-scale educational innovation projects and their explanatory foundations. Belgium's comprehensive Renewed Primary School project involving 275 schools illustrates the link between theory and practice. Vaguely formulated project goals encourage differing innovative configurations among schools, which are additionally influenced by the principal's role. Interviews with teachers from 24 schools revealed 4 types of local innovation policy emphasis: planning, interaction, risk avoidance, and cooptation. Each school's level of implementation was assessed from teaching activities data and project ratings. Analysis indicates that principals intervene differently in schools with a high level of implementation compared to schools with a low level of implementation. The search for the relationship between interventions and implementation involves locating an underlying explanatory factor that "creates meaning." Perceiving leadership as a language game suggests that language is the vehicle conveying meaning. Understanding the interconnections between explanatory factors provides a conceptual basis for prediction and for action-oriented studies because research and practice are linked--and are testable--through mutual feedback. Seventeen references are appended. (CJH)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (Washington, DC, April 20-24, 1987).
Researchers.
Administrators.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Role; Demonstration Programs; Educational Innovation; Elementary Education; Foreign Countries; Interviews; Leadership Responsibility; Organizational Change; Organizational Theories; Policy Formation; Principals; Program Development; Research Utilization; School Effectiveness; School Organization; Theory Practice Relationship; Belgium; Policy Implementation; Reports, Research; Speeches/Meeting Papers